Politics as "customer relations" - Dumitrica, Delia (Javnost (Ljubljana), 2014)
A political leader's authenticity has always been a site of struggle: politicians have tried to control their own image, while mass media has promised to reveal the "real" self behind the electoral campaign. In recent years, social media such as Facebook, Twitter or YouTube have gained a positive reputation as electoral tools. This paper seeks to critically engage with this reputation, by focusing on how these services become discursively articulated with the notion of political "authenticity" in the case of the 2010 municipal elections in Calgary, Canada. In these elections, the intense use of social media by the winning candidate has been seen as proof of the democratic power of these communication technologies to bring together politicians and citizens. A qualitative thematic analysis of 86 undergraduate essays reveals how participants collectively talked about political "authenticity." The paper argues that political ""authenticity" becomes articulated as a result of the intrinsic features of social media, reinforcing the longstanding technological determinist view of technology as the guarantor of a better citizen/politician relation. The discursive articulation of social media and political "authenticity" portrays politics as a customer relations service, providing little insight into how we are to understand and relate to democratic politics after elections.
Keywords: politics; politika; politiki; communication; komuniciranje; komunikacijska tahnologija; javnost; odnosi z javnostmi; mass media; množični mediji; javno mnenje; politična kampanja; lokalne volitve; Kanada; Canada